Can you prove this using mathematical induction?

1/2+2/(2^2)+3/(2^2)+...+n/(2^n)=2- (n+2)/(2^n)

2 Answers

What you need to do is:
1) prove that it holds for n=1
2) prove that, if it holds for n-1, then it holds for n, where n>1

Explanation:

1) the first statement is easy to check, we just need to use n=1. Doing so, we have 1/2 = 2 - (1+2)/2^1 = 2-3/2 = 1/2, which is true.

2) now, for the second statement, let's suppose it holds for n-1. If so, we have 1/2 + ... + (n-1)/2^(n-1) = 2 - ((n-1)+2)/2^(n-1).

Therefore, 1/2 + ... + (n-1)/2^(n-1) + n/2^n = 2 - ((n-1)+2)/2^(n-1) + n/2^n, but we can rewrite the right hand side as

2 - ((n-1)+2)/2^(n-1) + n/2^n = 2 - (2(n-1)+2*2-n)/2^n =

2 - (2*n-2+4-n)/2^n = 2 - (n+2)/2^n//

So, by the Induction Principle, the equation holds for any n>=1

Hope it helps.

Oct 13, 2017

I assume there is an error in the given sum and the 3^(rd) term should in fact read 3/2^3 rather than 3/2^2

Induction Proof - Hypothesis

We seek to prove that:

1/2 + 2/2^2 + 3/2^3 + ... + n/2^n = 2-(n+2)/2^n

Which can also be written as:

sum_(k=1)^n \ k/2^k = 2-(n+2)/2^n ..... [A]

So let us test this assertion using Mathematical Induction:

Induction Proof - Base case:

We will show that the given result, [A], holds for n=1

When n=1 the given result gives:

LHS = sum_(k=1)^1 \ k/2^k = 1/2^1=1/2
RHS = 1(4-1)/3 = 2-(1+2)/2^1 = 2-3/2 1/2

So the given result is true when n=1.

Induction Proof - General Case

Now, Let us assume that the given result [A] is true when n=m, for some m in NN, m gt 1, in which case for this particular value of m we have:

sum_(k=1)^m \ k/2^k = 2-(m+2)/2^m ..... [B]

Consider the LHS of [A] with the addition of the next term, in which case we have

LHS = sum_(k=1)^(m+1) \ k/2^k
\ \ \ \ \ \ \ \ = (sum_(k=1)^(m) \ k/2^k) + (m+1)/2^(m+1)
\ \ \ \ \ \ \ \ = 2-(m+2)/2^m + (m+1)/2^(m+1) \ \ \ using [B]
\ \ \ \ \ \ \ \ = 2 - (2(m+2))/(2 * 2^m) + (m+1)/2^(m+1)
\ \ \ \ \ \ \ \ = 2 - (2m+4)/(2^(m+1)) + (m+1)/2^(m+1)
\ \ \ \ \ \ \ \ = 2 - ((2m+4)-(m+1))/(2^(m+1))
\ \ \ \ \ \ \ \ = 2 - ((2m+4-m-1))/(2^(m+1))
\ \ \ \ \ \ \ \ = 2 - (m+3)/(2^(m+1))
\ \ \ \ \ \ \ \ = 2 - ((m+1)+2)/(2^(m+1))

Which is the given result [A] with n=m+1

Induction Proof - Summary

So, we have shown that if the given result [A] is true for n=m, then it is also true for n=m+1 where m gt 1. But we initially showed that the given result was true for n=1 so it must also be true for n=2, n=3, n=4, ... and so on.

Induction Proof - Conclusion

Then, by the process of mathematical induction the given result [A] is true for n in NN

Hence we have:

1/2 + 2/2^2 + 3/2^3 + ... + n/2^n = 2-(n+2)/2^n QED